2012
DOI: 10.1002/jcb.24127
|View full text |Cite
|
Sign up to set email alerts
|

Ciliogenic RFX transcription factors regulate FGF1 gene promoter

Abstract: Fibroblast growth factor 1 (FGF1) has been shown to regulate cell proliferation, cell division, and neurogenesis. Human FGF1 gene 1B promoter (-540 to +31)-driven green fluorescence (F1BGFP) was shown to recapitulate endogenous FGF1 gene expression. It can also be used to isolate neural stem/progenitor cells (NSPCs) and glioblastoma stem cells (GBM-SCs) from developing mouse brains and human glioblastoma tissues, respectively. However, the regulatory mechanisms of FGF-1B promoter and F1BGFP(+) cells are not cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“… 74 Interestingly, RFX1, RFX2 and RFX3 cooperate to modulate the maintenance of neural progenitors and GSCs through regulating fibroblast growth factor 1 (FGF1) promoter activity, an important mitogen for neurogenesis. 75 , 76 It would be necessary to explore whether RFX1 mediates GBM progression through primary cilia, since this possibility was not addressed in the abovementioned studies. In this sense, although the biological role of RFX1 is not well defined and includes regulation of ciliary and non-ciliary targets, 72 RFX1 and RFX2 were recently demonstrated to regulate the transcription level of ALMS1 gene, which encodes a protein localized to basal bodies and centrosomes that is mutated in Alström syndrome, a ciliopathy.…”
Section: Linking Primary Cilium and Glioblastoma: Current Evidencementioning
confidence: 99%
“… 74 Interestingly, RFX1, RFX2 and RFX3 cooperate to modulate the maintenance of neural progenitors and GSCs through regulating fibroblast growth factor 1 (FGF1) promoter activity, an important mitogen for neurogenesis. 75 , 76 It would be necessary to explore whether RFX1 mediates GBM progression through primary cilia, since this possibility was not addressed in the abovementioned studies. In this sense, although the biological role of RFX1 is not well defined and includes regulation of ciliary and non-ciliary targets, 72 RFX1 and RFX2 were recently demonstrated to regulate the transcription level of ALMS1 gene, which encodes a protein localized to basal bodies and centrosomes that is mutated in Alström syndrome, a ciliopathy.…”
Section: Linking Primary Cilium and Glioblastoma: Current Evidencementioning
confidence: 99%
“…We demonstrated that knockdown of FGF1 decreases sphere formation in GBM cells [48] . Recently, in our other report, blocking of FGF1/FGFR by small molecule, SU5402, results in decreased sphere forming capacity in GBM cells [28] .…”
Section: Development Of Methods For Isolation Of Gbm-scs Frommentioning
confidence: 73%
“…Alterations in RFX1 expression are associated with several cancer types, including glioblastomas, breast cancer and a subset of lymphomas . It has been shown that RFX1 down‐regulates expression of the proto‐oncogene MYC , transforming growth factor‐β2 ( TGFβ2 ) as well as CD44 , a hyaluronic acid cell surface receptor .…”
Section: Rfx Factors In Cancermentioning
confidence: 99%